2017
DOI: 10.1186/s12876-017-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of celiac disease and applicability of ESPGHAN guidelines in Mediterranean countries: a real life prospective study

Abstract: BackgroundWe assessed how the diagnosis of Celiac Disease (CD) is made and how the new ESPGHAN guidelines can be applied in children from countries with different resources.MethodsA real life prospective study was performed in 14 centres of 13 different Mediterranean countries. Participants were asked to apply the usual diagnostic work-up for CD according to their diagnostic facilities.ResultsThere were 1974 patients enrolled in the study, mean age 4 years, 10 months; 865 male, 1109 female. CD was confirmed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
(14 reference statements)
4
16
0
Order By: Relevance
“…In the current study, more severe duodenal histology was noted in seropositive patients based on Marsh-Oberhuber classification ( P =0.002). This finding was also reported by other studies in which the severity of small intestinal damage on histology was correlated with tTG IgA levels [ 10 , 32 , 33 ]. A study from Iraq showed a significant reduction in the levels of CD-specific antibodies along with histological remission after GFD which also support our finding [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, more severe duodenal histology was noted in seropositive patients based on Marsh-Oberhuber classification ( P =0.002). This finding was also reported by other studies in which the severity of small intestinal damage on histology was correlated with tTG IgA levels [ 10 , 32 , 33 ]. A study from Iraq showed a significant reduction in the levels of CD-specific antibodies along with histological remission after GFD which also support our finding [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…There is evidence from retrospective studies that levels of anti-TTG IgA IgA ≥10× ULN are sufficient to diagnose CD without positive EMA, providing PPVs between 95.9 and 100%, 11,[13][14][15][16] although other studies have found lower PPVs. 17,18 The other important issue that has arisen from these studies is the finding of false-positive cases when single tests are used for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from retrospective studies that levels of anti‐TTG IgA IgA ≥10× ULN are sufficient to diagnose CD without positive EMA, providing PPVs between 95.9 and 100%, 11,13–16 although other studies have found lower PPVs 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…To date, histology of intestinal biopsy is the gold standard for the diagnosis of CD and confirming complete response to GFD in many regions because other diagnostic procedures maybe unavailable. 55 However, upper endoscopy is an invasive, expensive procedure, and repeating endoscopy for follow-up of the response of patients to GFD is inconvenient to many patients. Thus, we investigated the clinical utility of other potential non-invasive methods for screening, diagnosis and follow-up of CD.…”
Section: Discussionmentioning
confidence: 99%